Redescription of Bakuella (Bakuella) marina Agamaliev and Alekperov, 1976 (Protozoa, Hypotrichia), With Notes on Its Morphology, Morphogenesis, and Molecular Phylogeny - Zhu, Rong; Zhang, Qi; Tang, Lan; Zhao, Yan; Li, Jingbao; Li, Fengchao (Frontiers in Microbiology, 2022)
Because the original description of Bakuella (Bakuella) marina, type of the genus, is only based on protargol-impregnated specimens, one of the important living features, namely, the presence/absence of cortical granules, remains unknown so far. In the present work, a detailed investigation of a Chinese population of B. (Bakuella) marina is carried out using the integrated approaches, and the live morphology, ontogenesis, and molecular information of B. (Bakuella) marina are presented for the first time. The infraciliature of this population corresponds perfectly with that of the original description. The in vivo observation indicates that B. (Bakuella) marina possesses colorless cortical granules. The most prominent morphogenetic feature of B. (Bakuella) marina is that the parental adoral zone of membranelles is completely replaced by the newly formed one of the proters. Molecular phylogenetic analysis based on a small subunit ribosomal gene (SSU rDNA) shows that five Bakuella species are clustered with the species from other six Urostylid genera, namely, Anteholosticha, Apobakuella, Diaxonella, Holosticha, Neobakuella, and Urostyla. The monophyletic probabilities of the family Bakuellidae, genus Bakuella, subgenus B. (Bakuella), and subgenus B. (Pseudobakuella) are rejected by the approximately unbiased test. This study further shows that the family Bakuellidae, genus Bakuella, and subgenus B. (Bakuella) are all nonmonophyletic groups. In order to establish a reasonable classification system, information on molecular and morphogenesis of more Bakuellids and its related species is urgently needed.